Hizbullah's Documents : From the 1985 Open Letter to the 2009 Manifesto. - Alagha, Joseph Elie (Amsterdam University Press, 2011)
A reliable reference work that includes accurate English translations of Hizbullah's primary documents with adequate commentaries and relevant background information that spans three decades.